Optimizing Vegetative Propagation of Litsea garciae Vidal: Effects of Cutting Source and Rootone-F Soaking Duration on Root and Shoot Development - Ekamawanti, Hanna Artuti; Hazelyna, Sania; Wulandari, Reine Suci (Jurnal Sylva Lestari, 2025)
Litsea garciae Vidal, commonly known as engkala, is an endemic medicinal plant of Borneo with promising pharmacological potential. Vegetative propagation through shoot cuttings is a practical alternative to overcome the challenges of seed-based propagation. This study investigated the effects of cutting material source (seedlings and saplings) and soaking duration in 50% Rootone-F (0, 15, 30, 45, and 60 minutes) on the rooting and shoot growth of L. garciae shoot cuttings. A factorial experiment with a completely randomized design was applied, involving ten treatment combinations with five replications each. Results showed that cuttings derived from seedlings achieved 100% survival and rooting rates regardless of Rootone-F treatment. In contrast, sapling cuttings achieved optimal rooting only after 15 minutes of soaking. The interaction of cutting source and soaking duration significantly influenced root development, while shoot growth varied only with individual treatments. Notably, seedling cuttings produced roots that were 1.3 times longer than those from sapling cuttings; however, the dry weight of sapling roots was 1.5 times greater. The dry weight of roots soaked in Rootone-F for 15 minutes significantly increased by 1.3 to 2.8 times compared to the dry weight of roots soaked for other durations. The seedling cuttings produced 1.2 times more shoots than saplings. Interestingly, cuttings without soaking treatment in Rootone-F produced the same number of new leaves as those soaked for 60 minutes but significantly more than those soaked for other durations. These results are vital for optimizing the vegetative propagation technique of L. garciae by selecting the appropriate cutting source and timing for Rootone-F immersion. Keywords: engkala, Litsea garciae, Rootone-F, shoot cuttings, vegetative propagation